Export tariffs in central African Countries - Bruce Cohen; Herbert Marks; Gustav Schachter (Intereconomics, 1971)
In recent years the export tariff has Increasingly been abandoned as a policy tool by the developed countries, yet it has been maintained by the less developed countries.
Keywords: 330; Foreign trade